Rapid assessment of myxomycetes in Isla Calero and Isla Brava, Costa Rica - Rojas Alavarado, Carlos Alonso (2022)
The geography of the northeasternmost section of Costa Rica corresponds to river islands sparsely populated and highly protected for biological conservation. Myxomycetes had not been studied in that part of such Central American country and the present rapid assessment project (RAP) represents the first attempt to do so. By studying moist chambers made with ground litter from both Isla Calero and Isla Brava, a total of 22 species of myxomycetes were identified in the lowland rainforests occupying this area. Of the total number of samples used to prepare moist chamber cultures, about 53% yielded positive results of myxomycete activity and the most commonly recorded species were Lamproderma scintillans and Arcyria cinerea. Surprisingly, Physarum roseum and P. virescens, two species more commonly found in the tropical dry forests of Costa Rica, were recorded as well. This study covered the section of the islands facing the inner part of the country and not the open Caribbean Sea, where the effect of winds and marine environments could be responsible for a different assemblage of fruiting myxomycetes.